2011
DOI: 10.1590/s1516-35982011001200022
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality during storage and deposition of minerals in eggs from quails fed diets supplemented with organic selenium, zinc and manganese

Abstract: -Three experiments with Japanese laying quails were performed aiming to assess the effect of supplementation with minerals in organic form on the egg quality during storage and the deposition of minerals in eggs. The assessments of each experiment were related to one mineral, thus, experiment 1 assessed the supplementation with selenium in 0.35-, 0.70-and 1.05-mg/kg levels of feed; experiment 2, the supplementation with zinc in 50-, 100-and 150-mg/kg levels of feed; and experiment 3, the supplementation of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Similar findings were reported in previous studies (Nkukwana et al, 2016;Qwele et al, 2013). Similar results were reported in the estimation of calcium in tibia bone and ash content with M. oleifera supplementation (Nkukwana et al, 2014b;Gravena et al, 2011). Feed supplemented with MPM significantly affected serum biochemistry (P ≤0.05).…”
Section: Tablesupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were reported in previous studies (Nkukwana et al, 2016;Qwele et al, 2013). Similar results were reported in the estimation of calcium in tibia bone and ash content with M. oleifera supplementation (Nkukwana et al, 2014b;Gravena et al, 2011). Feed supplemented with MPM significantly affected serum biochemistry (P ≤0.05).…”
Section: Tablesupporting
confidence: 90%
“…Selenium and methionine have a close relationship in metabolism. Birds supplemented only with methionine (3.2, 4.0, and 5.4g/kg) without selenium showed 0.48, 0.63, and 0.62 µg/g of deposited selenium in egg yolk, whereas this deposition was increased with an increment of selenium (Wang et al, 2010;Gravena et al, 2011). An organic form of selenium can easily enrich eggs, as was shown in a study conducted by Bennett and Cheng, (2010), in which they used sodium selenite (0.3 µg Se/g of feed) along with selenium yeast SSAF-600 ® (Diamond V Mills, Cedar Rapids, IA, USA), an organic source with the concentrations 1.0, 2.4, and 5.1 µg Se /g of diet.…”
Section: Tablementioning
confidence: 99%
“…The discrepancies in relative bioavailability between various organic Mn sources could be explained by different chemical characteristics and chelation strength of commercial organic Mn feed additives (Li et al, 2004). Gravena et al (2011) observed an increase in the Mn content of egg yolk from quails supplemented with 60, 120, and 180 mg Mn/kg feed from an organic source. According to Mabe et al (2003), feed supplementation with Mn levels at 30 or 60 mg/kg from its inorganic (MnO) and organic (Mn amino acid complex) sources resulted in higher deposition of this trace element in the yolk of eggs from hens receiving greater amounts of Mn in their diet, regardless of its source.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gravena et al (2011), organic selenium, in the form of selenium-methionine, influences egg quality, since it participates in the synthesis of proteins deposited in the albumen.…”
Section: Discussionmentioning
confidence: 99%